Projeto e implementação de um controle modular HCC para integração de fontes alternativas de energia - Barros Neto, José Paulo de (2006)
The experience of electric energy shortage in 2001 demonstrated that our dependence almost exclusively on hydroelectricity could fetch great problems to Brazil. Thus being, the existence of trustworthy alternatives of energy must exist, at the very least, as a reserve. For this reason, the perspective of decentralizing the energy production as a form of promoting the socioeconomic development of remote communities not connected to the public distribution system as well for mass production of electricity, are the motivations of this work. Such situation justified the analysis of performance and development of the integration of diverse types of alternative primary sources by transforming them into current sources as a means of preventing the circulation of current due to voltage differences across the sources. Control of the load voltage uses the modulation of a secondary load in parallel with a primary load in such a way that current excesses from the current sources are drained only through the secondary load, remaining unchanged the conditions for the primary load. To manage the voltage and current distribution in the main load, a module, dedicated and expandable controller is proposed for hybrid systems of electric energy generation such as those using wind-solar-storage for generation of electric energy in a trustworthy form, unassisted and independent. The proposed integrated system of energy does allow the control and integration of the most usual forms of energy generation such as hydraulic, wind, storage of energy, specially, in batteries. The control program is also adjusted to integrate other forms of generation, independent of its origin. The control as a whole is based on the algorithm "Hill Climbing Control" (HCC) for individual maximization of the generated power and rotation in each source and regulating the voltage across the load, in order to get the best advantage from the installations. In this dissertation is also shown some practical results about the proposed theory on a prototype of control based on the micro controller PIC18F452 for distribution of energy from a power plant of electric energy generation installed and operating in the CEEMA-UFSM campus. Furthermore, the controller module of power as presented in this work is more useful among others because it allows the use of hybrid electronics and microelectronics that are able of concentrating several circuits in a only "chip", including control functions for power conversion, A/D devices, program memory, data memory, modules for capture and comparison, timers and PWM modules.